Radar Forward Operator for Verification of Cloud Resolving Simulations within the COSMO Model - Jerger, Dorit (Wissenschaftliche Berichte des Instituts für Meteorologie und Klimaforschung des Karlsruher Instituts für Technologie, 2013)
In this work, various simulation methods of the effective radar reflectivity factor and its attenuation by atmospheric particles from the variables of the COSMO model have been implemented within a so-called radar forward operator, and its output was compared to measurements from the German radar network. To perform a statistically reliable model verification, contoured frequency by altitude diagrams (CFADs) were used and refined.